ChemInform Abstract: [2 + 2] Cycloaddition of Electron‐Poor Acetylenes to Enaminones, Enamino Esters and Related Systems. Rearrangements and Ring‐Expansion Reactions. Issue 14 (8th April 2014) - Stanovnik, Branko
Abstract Review: 115 refs.